African Edible Insects as Alternative Source of Food, Oil, Protein and Bioactive Components 2020
DOI: 10.1007/978-3-030-32952-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Insects as Food in Africa

Abstract: This publication is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…Over many years, indigenous African insect consumers have mastered skills of harvesting edible insects from the wild. Chavhunduka (2) documented several traditional methods used for harvesting edible insects from the wild in Zimbabwe while van Huis (31) and DeFoliart (32) recorded traditional approaches used in different parts of Africa. Documented records provide evidence that most of the traditional harvesting methods are based on knowledge of insect life-history strategies (such as patterns of survival, feeding and reproduction) by local gatherers.…”
Section: Is There Evidence For Good Stewardship Of Edible Insects' Utilization In Ssa? Evidence From Harvesting Methods From the Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…Over many years, indigenous African insect consumers have mastered skills of harvesting edible insects from the wild. Chavhunduka (2) documented several traditional methods used for harvesting edible insects from the wild in Zimbabwe while van Huis (31) and DeFoliart (32) recorded traditional approaches used in different parts of Africa. Documented records provide evidence that most of the traditional harvesting methods are based on knowledge of insect life-history strategies (such as patterns of survival, feeding and reproduction) by local gatherers.…”
Section: Is There Evidence For Good Stewardship Of Edible Insects' Utilization In Ssa? Evidence From Harvesting Methods From the Wildmentioning
confidence: 99%
“…Van Huis (6) and DeFoliart (32) provided extensive details on processing methods by indigenous communities in Africa. Evidence from recent documentations in parts of southern Africa (37,42,43), van Huis (31) indicates that several of the old traditions are still being practiced in modern insect consumption activities.…”
Section: Evidence From Insect Traditional Processing and Preparation Methods Of Consumptionmentioning
confidence: 99%
“…Still, it should be stressed that the "international" species seem to have originated from the pet food sector and by chance also resulted suitable for human consumption (Costa Neto and Ramos Elorduy, 2006;Grabowski, 2017;Van Huis, 2020;Magara et al, 2021). Locusts, such as migratory (L. migratoria) and desert (S. gregaria) locusts are traditionally mostly consumed in times of invasion when swarms offer a large amount of available insects.…”
Section: Constraint Examplesmentioning
confidence: 99%
“…Although it is not proven that all productive insects can experience distress and pain (resp. to which extend), it is being suggested that they should be farmed and killed using the precautionary principle, which means that the Brambell's five freedoms (Table 6) do apply to them and must be observed mandatorily, regardless of consumer expectations (Van Huis, 2020).…”
Section: Consumer Awareness and Acceptancementioning
confidence: 99%
“…Eating insects is a part of local culture for at least 2 billion people in about 113 countries [1,2,3,4], and Africa accounts for over 120 million insect eaters [5]. Of the 2,111 edible insect species known globally [6], around 500 species have been reported in sub-Saharan Africa [7,8]. In Africa, edible insects are mainly collected from the wild for household consumption and informal trade [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%